Theoretical and Experimental Investigation of the Effect of Linear Fluid Power Control System Design on its Static and Dynamic Performance - Qassim, A. I.; Sadak, Tahany W.; Rizk, Mahassen (International Journal of Robotics and Control Systems, 2025)
Fluid power control systems are widely used in automated systems like manufacturing, biomedical treatments, and food handling, as well as in optimizing aircraft wing design, mobile applications, and thermal management in electronic devices, energy transformation, and aerospace applications. This study investigated the static and dynamic characteristics of a linear fluid power control system utilizing either a servo control valve (SV) or a proportional directional flow control valve (PV). The study focused on evaluating performance differences between these two valve types while maintaining a constant oil temperature at 30Â°C. Experimental tests were conducted under varying supply pressures, loads, and valve types. A system was built to conduct real-time experiments. In this paper we studied the effect of valve flow rate at full opening, the actual supply pressure-decay, and studied the effect of the loading system on the performance. The aim of this paper is to find out which control valve is better in static and dynamic performance in real-world. Through comparing two hydraulic control valves designs, the experiment results show that the servo control valve (SV) offers a clear advantage over the proportional directional flow control valve (PV) in linear fluid power control systems operating at a constant temperature. The SV designs demonstrated superior performance in terms of flow rate, pressure retention, and dynamic response. This makes SV an optimal choice for applications requiring high flow rates, consistent pressure, and precise, rapid adjustments, especially in high-speed operations.